Pengaruh transfer pricing dan capital intensity terhadap tax avoidance dengan leverage sebagai variabel moderasi - Muhammad Refa Pamungkas; Dade Nurdiniah (LPMP Imperium, 2025)
This research aims to determine the effect of transfer pricing and capital intensity on tax avoidance with leverage as moderating variable on company in companies listed on the Indonesia Stock Exchange for the 2022-2024 periode. The sampling technique used purposive sampling and obtained 22 companies. This research used quantitative and analitycal method in this research uses multiple regression analysis and moderated regression analysis. The result of research tested using application Statistic Package The Social Science (SPSS26). The result of this study show that : transfer pricing has no effect on tax avoidance, capital intensity has effect on tax avoidance, leverage is able to moderate the influence of transfer pricing on tax avoidance, leverage is not able to moderate the influence of capital intensity on tax avoidance. Public interest statements This research can provide benefits for companies, regulators, and academics in understanding and managing tax avoidance practices, transfer pricing, capital intensity, and leverage. As well as an encouragement for business practices to be more responsible and also compliant in terms of taxation.